Employing Technical and Legal Means to Protect Databases (مجلة المنصور, 2022)
The prevalence of inexpensive and powerful computer systems and storage has led to the gathering of unprecedented amounts of data by organizations from all facets of daily life .This intelligent data gathering in a manual or a computer form as well as its advanced processing are, generally called database. Data bases play an important role in the development of information market and its products. A large number of databases are available online from foreign vendors which now find an increasing market in the country. Authors or developers are interested in receiving remuneration from databases which are based on intellectual and skillful inputs. Thus, they want to restrict copying from databases while the users are keen to make use of the information either without paying for it or through having copying rights at relatively lesser cost. This study presents a new paradigm for thinking about intangible property rights in response to recent criticism that information products such as databases should not be over-propertied. This study shows two main types of available protection: technical protection and legal one.